Effects of benzoic acid synthesized from Cinnamomum cassia by green chemistry on valproic acid-induced neurotoxicity in zebrafish embryos - ALTURFAN, EBRU IŞIK (My University, 2024)
Benzoic acid, the most basic aromatic carboxylic acid, is produced industrially and used in cosmetic, hygiene, and pharmaceutical items as a flavoring ingredient and/or preservative. The significance of sodium benzoate, a metabolite of cinnamon, used as a food preservative and FDA-approved medication to treat urea cycle abnormalities in humans, has been shown to raise the levels of neurotrophic factors. Valproic acid (VPA), a commonly used anti-epileptic and mood-stabilizing medication, causes behavioral and intellectual problems and is a commonly used agent to induce animal model for autism. Aim of this study is to determine the effects of benzoic acid synthesized from Cinnamomum Cassia by green chemistry method on gene expressions related to autism development in case of VPA toxicity. Zebrafish embryos were exposed to low and high doses of benzoic acid for 72 h post-fertilization. Locomotor activities were determined. Acetylcholinesterase (AchE), lipid peroxidation, nitric oxide (NO), sialic acid (SA), glutathione (GSH)-S-transferase, catalase (CAT), and superoxide dismutase (SOD) activities were determined spectrophotometrically. eif4b, adsl, and shank3a expressions were determined by RT-PCR as autism-related genes. Although high-dose benzoic acid inhibited locomotor activity, benzoic acid at both doses ameliorated VPA-induced disruption in oxidant-antioxidant balance and inflammation in zebrafish embryos and was effective in improving the impaired expression of autism-related genes.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; TOKSİKOLOJİ; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; TOXICOLOGY; Toksikoloji; Sağlık, Toksikoloji ve Mutajenez; Fizik Bilimleri; Toxicology; Health, Toxicology and Mutagenesis; Physical Sciences; Benozic acid; Cinnamomum cassia; green chemistry; valproic acid; zebrafish embryo